FEATURES OF PEDAGOGICAL TECHNOLOGIES REHABILITATION OF JUNIOR SCHOOLCHILDREN IN RURAL SCHOOLS IN THE PROCESS OF PHYSICAL EDUCATION - Djalolov Sherzod Valiyevich (Journals Park Publishing, 2023)
The article deals with certain aspects of the essence and features of pedagogical technologies for improving the health of primary school children in the process of physical education in a rural school. A pedagogical technology for improving the health of rural schoolchildren in the process of physical education is proposed, which includes the basic accompanying technologies.
Keywords: pedagogical technology, health improvement, physical education, junior schoolchildren, rural society.